An Analysis of Approved Foreign Direct Investment in Hydropower of Nepal - Binadi, Tek Raj (Contemporary Research: An Interdisciplinary Academic Journal, 2023)
Hydropower is the major economic sector of Nepal. This paper analyzed approved FDI in hydropower sector based on secondary data 2004-2022. Descriptive research design has been used. The quantitative data presented in tabular form. Bar-diagram and flow chart used as required in analysis. Domestic financial resources are not sufficient to generate electricity. Due to this government of Nepal realized FDI in this sector. The government promotes and facilitates FDI by introducing appropriate policies, legal and institutional arrangements to create an enabling environment for domestic as well as foreign investors. Foreign investors are playing important role for hydroelectricity generation. Upper Bhotekoshi and Khimti project are developed By FDI. This study shows that the status of approved FDI on hydropower sector is increasing since 2004 to 2022 (except 2004-05, 2006-07, 2016-17, 2018-19 and 2021-22) with respect to total approved FDI in Nepal. It clearly state that foreign investors are interested to invest in this sector but there are some obstacle for them. If the government provides more secure environment to foreign investors they will be highly encouraged to invest in this sector.